Association between osteoarthritis-related serum biochemical markers over 11 years and knee MRI-based imaging biomarkers in middle-aged adults. Issue 5 (May 2022) - Singh, A.; Venn, A.; Blizzard, L.; Jones, G.; Burgess, J.; Parameswaran, V.; Cicuttini, F.; March, L.; Eckstein, F.; Wirth, W.; Ding, C.; Antony, B.
Summary: Objective: To describe the associations between osteoarthritis (OA)-related biochemical markers (COMP, MMP-3, HA) and MRI-based imaging biomarkers in middle-aged adults over 10–13 years. Methods: Blood serum samples collected during the Childhood Determinants of Adult Health (CDAH)-1 study (year:2004–06; n  = 156) and 10–13 year follow-up at CDAH-3 ( n  = 167) were analysed for COMP, MMP-3, and HA using non-isotopic ELISA. Knee MRI scans obtained during the CDAH-knee study (year:2008–10; n  = 313) were assessed for cartilage volume and thickness, subchondral bone area, cartilage defects, and BML. Results: In a multivariable linear regression model describing the association of baseline biochemical markers with MRI-markers (assessed after 4-years), we found a significant negative association of standardised COMP with medial femorotibial compartment cartilage thickness (β:-0.070; 95%CI:-0.138, -0.001), and standardised MMP-3 with patellar cartilage volume (β:-141.548; 95%CI:-254.917, -28.179) and total bone area (β:-0.729; 95%CI:-1.340, -0.118). In multivariable Tobit regression model, there was a significant association of MRI-markers with biochemical markers (assessed after 6–9 years); a significant negative association of patellar cartilage volume (β:-0.001; 95%CI:-0.002, -0.00004), and total bone area (β:-0.158; 95%CI-0.307, -0.010) with MMP-3, and total cartilage volume (β:-0.001; 95%CI:-0.001, -0.0001) and total bone area (β:-0.373; 95%CI:-0.636, -0.111) with COMP. No significant associations were observed between MRI-based imaging biomarkers and HA. Conclusion: COMP and MMP-3 levels were negatively associated with knee cartilage thickness and volume assessed 4-years later, respectively. Knee cartilage volume and bone area were negatively associated with COMP and MMP-3 levels assessed 6–9 years later. These results suggest that OA-related biochemical markers and MRI-markers are interrelated in early OA.